DINAMIKA PERANCANAAN PEMBANGUNAN DESA PARTISIPATORIS (Studi, Keterlibatan Pemangku Kepentingan di Desa Tate.Kecamatan Darume Utara Kabupaten Halmahera Utara) - Faisal Hi. Kadir; Ali Lating; Raoda M Jae; Fathnun Tan (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
Abstract The rural infrastructure development acceleration program in this research aims to improve the quality of infrastructure development and empower the community with large community involvement. The aim of this research is to determine the level of effectiveness and analyze the Tate Village government in development. To measure the level of effectiveness of researchers using the research method used in this research is a qualitative research method. The results obtained from observation, interviews and documentation, in this research, are Tate Village which is the location for research in village development. The research results show that the dynamics of development planning in Tate Village are going well, this can be seen from the presence of stakeholders to realize quality planning. The importance of participation can be seen from the priority programs implemented in the form of footpaths and connecting bridges between RTs. External constraints such as the level of knowledge and time available to be involved in development planning as well as internal factors such as the level of poverty and competition between fellow residents in viewing development programs in Tate Village.